Perkembangan Pembiayaan Bank Syariah Sebelum dan Sesudah Pandemi COVID-19 - Patoni, Lalu Rian; Cahyaningtias, Susi Retna (Jurnal Riset Akuntansi, 2025)
This study examines the development of Islamic financing contracts at Bank NTB Syariah from 2019 to 2024, focusing on shifts in contract dominance before, during, and after the Covid-19 pandemic. Using a descriptive-comparative time approach and based on the theory of financial intermediation, the research analyzes five financing contracts: murabahah, musyarakah, mudharabah, qardh, and ijarah. The findings reveal a significant shift in the bank’s financing structure, with musyarakah emerging as the dominant contract, increasing steadily from IDR 311 billion in 2019 to IDR 1.12 trillion in 2024. In contrast, murabahah declined sharply, while mudharabah and qardh played only minor roles. Ijarah was not recorded during the entire observation period. The results suggest a strategic shift toward partnership-based contracts to better accommodate business risk and economic uncertainty. This transformation supports the relevance of Islamic financial intermediation theory and highlights the adaptive role of regional Islamic banks during times of economic crisis.